The effects of low-volume high-intensity interval training and circuit training on maximal oxygen uptake - Birkett, Stefan T.; Nichols, Simon; Sawrey, Richard; Gleadall-Siddall, Damien; McGregor, Gordon; Ingle, Lee (Sport Sciences for Health, 2019)
Purpose High-intensity interval training (HIIT) and circuit training (CT) are popular methods of exercise, eliciting improvements in cardiorespiratory fitness (CRF). However, direct comparisons of these two training methods are limited. We investigated the effects of HIIT and CT on CRF. Methods Thirty-nine apparently healthy middle-aged participants [HIIT; mean age: 42.5 ± 12.3; V˙O2max 31.5 ± 7.1 (ml kg−1 min−1); 52% males; CT; mean age: 41.2 ± 12.9; V˙O2max 31.4 ± 6.8 (ml kg−1 min−1); 57% males] were randomly allocated to two sessions per week of HIIT or CT over 8 weeks. HIIT performed ten 1-min cycle-ergometry intervals at > 85% HRmax, separated by ten 1-min intervals of active recovery. The CT group performed up to 40-min of CT at 60–80% HRmax. CRF was measured using maximum oxygen uptake ( V˙O2max ), ventilatory anaerobic threshold ( V˙O2 at VAT) and maximum oxygen pulse ( V˙O2 /HR).
Keywords: Cardiorespiratory fitness; Fidelity; Maximal oxygen consumption; V̇O2max; Ventilatory anaerobic threshold; HIIT